Nickel cobalt sulfide nanoneedle array as an effective alternative to pt as a counter electrode in dye sensitized solar cells - Banerjee, Abhik; Upadhyay, Kush Kumar; Bhatnagar, Sumit; Tathavadekar, Mukta; Bansode, Umesh P.; Agarkar, Shruti A.; Ogale, Satishchandra B. (RSC Advances, 2014)
Self supported nickel cobalt sulfide (NCS) nanoneedles are directly formed on FTO glass substrates by sulphurization of nickel cobalt oxide nanoneedles (grown by a hydrothermal method) in the presence of a hydrogen sulfide and argon gas mixture. These NCS nanoneedles when used as a counter electrode for dye sensitized solar cells (DSSCs) show efficient catalytic activity towards the I-/I-3(-) redox couple, and lead to an impressive efficiency of 6.9%, compared with 7.7% obtained with a Pt electrode in similarly constructed devices.